Effect of tool-use observation on metric body representation and peripersonal space. (November 2020) - Galigani, M.; Castellani, N.; Donno, B.; Franza, M.; Zuber, C.; Allet, L.; Garbarini, F.; Bassolino, M.
Abstract: In everyday life, we constantly act and interact with objects and with others' people through our body. To properly perform actions, the representations of the dimension of body-parts (metric body representation, BR) and of the space surrounding the body (peripersonal space, PPS) need to be constantly updated. Previous evidence has shown that BR and PPS representation are highly flexible, being modulated by sensorimotor experiences, such as the active use of tools to reach objects in the far space. In this study, we investigate whether the observation of another person using a tool to interact with objects located in the far space is sufficient to influence the plasticity of BR and PPS representation in a similar way to active tool-use. With this aim, two groups of young healthy participants were asked to perform 20 min trainings based on the active use of a tool to retrieve far cubes (active tool-use) and on the first-person observation of an experimenter doing the same tool-use training (observational tool-use). Behavioural tasks adapted from literature were used to evaluate the effects of the active and observational tool-use on BR (body-landmarks localization task-group 1), and PPS (audio-tactile interaction task – group 2). Results show that after active tool-use, participants perceived the length of their arm as longer than at baseline, while no significant differences appear after observation. Similarly, significant modifications in PPS representation, with comparable multisensory facilitation on tactile responses due to near and far sounds, were seen only after active tool-use, while this did not occur after observation. Together these results suggest that a mere observational training could not be sufficient to significantly modulate BR or PPS. The dissociation found in the active and observational tool-use points out differences between action execution and action observation, by suggesting a fundamental role of the motor planning, the motor intention, and the related sensorimotor feedback in driving BR and PPS plasticity. Highlight: Does observational tool-use affect body and peripersonal space representations? A longer perceived arm length is reported after active but not observational tool-use. Active, but not observational tool-use induces a peripersonal space remapping. Observational tool-use could be not sufficient to affect body and space representations. Motor intention and the related sensory feedback seem necessary to alter these representations.